Smart Technological Learning Conceptual model - Sarma, Cakula (International Journal of Engineering and Technology, 2018)
Lifelong learning in one of most important aspects of nowdays educational system, which is understood as continuation of the previously acquired education and the enrichment of the professional skills according to the demands of the vocation in question. It is very important to figure out the most effective technological solutions and principal directions for implementing work-based learning strategies in the learning process. Â New smart learning individually oriented methodology has been developed based on human individual perception for fast growing information and big data society.Â Â